The Impact of beliefs and challenges faced, on the reported practice ofprivate school science teachers in abu dhabi - Mcmınn, Melissa; Kadbey, Hanadi; Dıckson, Martina (Journal of Turkish Science Education, 2015)
Private international schools in Abu Dhabi, UAE, are diverse in curriculum, methods and ethos. They all recruit internationally (and often Western) trained teachers. It could be assumed that these teachers bring with them beliefs about current ‘best practices’ from their native countries and that these methodologies are implemented into Abu Dhabi’s schools. This study used a mixed-methods survey design to investigate the reported beliefs and practices in science education, an area that primary teachers are often hesitant to approach, to identify how much impact beliefs have on reported practice, often despite impeding barriers and challenges. It was found that in many areas the reported beliefs and practices of Abu Dhabi’s private school teachers correlate. Where practice does not correlate with beliefs, language barriers and a lack of time, space and resources were identified as the leading reasons. Targeted professional development, support from school management and greater parental involvement are identified as strategies for reducing discrepancies between beliefs and practices.